Enhancing Local Capacities for Stormwater Management in Nassau, New Providence, The Bahamas. - Elwell, Holly.; Gove, Michael.; Latham, Daniel.; Ohikata, Makito.; Resnick, Katie.; Rugambwa, Paul. (Tufts University. Tisch Library., 2018)
2008 M.A. in Urban and Environmental Policy and Planning Field Project. Client: College of The Bahamas.